Early appearance and possible functions of non-neuromuscular cholinesterase activities - Falugi, Carla (Frontiers in Molecular Neuroscience, 2012)
The biological function of the cholinesterase (ChE) enzymes has been studied since the beginning of the twentieth century. Acetylcholinesterase plays a key role in the modulation of neuromuscular impulse transmission in vertebrates, while in invertebrates pseudo cholinesterases are preeminently represented. During the last 40 years, awareness of the role of ChEs role in regulating non-neuromuscular cell-to-cell interactions has been increasing such as the ones occurring during gamete interaction and embryonic development. Moreover, ChE activities are responsible for other relevant biological events, including regulation of the balance between cell proliferation and cell death, as well as the modulation of cell adhesion and cell migration. Understanding the mechanisms of the regulation of these events can help us foresee the possible impact of neurotoxic substances on the environmental and human health.